Clients' Pretreatment Role Expectations, the Therapeutic Alliance, and Clinical Outcomes in Outpatient Therapy. Issue 7 (29th October 2013) - Patterson, Candace L.; Anderson, Timothy; Wei, Christina
<x xml:space="preserve">Abstract</x> Objectives The present study examined the associations between pretreatment role expectations, working alliance, and therapy outcome. A mediational model was hypothesized wherein the therapeutic alliance mediates the relationship between clients' pretreatment role expectations and psychotherapy outcome. Method Sixty‐eight clients completed the Expectations About Counseling‐Brief Form at pretreatment, the Working Alliance Inventory‐Short Form Revised after Session 3, and the Outcome Questionairre‐45 at both pretreatment and the final session. Results All 3 expectations factors (Personal Commitment, Facilitative Conditions, Counselor Expertise) were related to the alliance. However, only expectations for Counselor Expertise were related to outcome, although this relationship did not appear to be mediated by the alliance. Conclusions Suggested research directions, clinical implications, and study limitations are discussed.